Millet crops as source of fodder - Bhat, B Venkatesh; Singode, Avinash; Balakrishna, D; Sooganna (Indian Farming, 2023)
India has the largest livestock population, however, the productivity of milk and other livestock product per animal is very low compared to other countries. One of the main reasons for the low productivity and performance of our livestock is malnutrition and under-nutrition owing to inadequate supply of nutritive fodder and feed. The country is highly deficient with respect to availability of green fodder, dry fodder and concentrates. The gaps for fodder supply are partly met by crop residues-straw and stovers. As the millets are the major cereals of dryland crops in arid and semi-arid regions, they form an important source of stover for the livestock of these regions.